The Kalinga Ethnic Identity Awareness - DR. JAMES S. GUIDANGEN (IJRDO - Journal of Social Science and Humanities Research, 2019)
Identity in terms of ethnicity, race, minority group status, gender, and sexual orientation is often constructed with class consciousness-group self-awareness in terms belonging to the same socioeconomic group. Moreover, it is a set of qualities and beliefs that make one person or group different from others. This study aimed to provide information on the views of the students of the Kalinga State University in terms of their Kalinga ethnic identity. The study determined that the students are much aware of their Kalinga ethnic identity however, the identified factors very much affected their identification. It is therefore recommended that schools may mandate the strict integration of the Kalinga history and culture in applicable subjects. On the other hand, the students/ the youth may start changing the negative perceptions of other people about the Kalingas. The Kalinga customs, practices and traditions that are deemed bad and have negative impacts must be changed or disregarded.